Vaccinia Virus Morphogenesis: A13 Phosphoprotein Is Required for Assembly of Mature Virions - Unger, Bethany (American Society for Microbiology, 2004)
The 70-amino-acid A13L protein is a component of the vaccinia virus membrane. We demonstrate here that the protein is expressed at late times of infection, undergoes phosphorylation at a serine residue(s), and becomes encapsidated in a monomeric form. Phosphorylation is dependent on Ser40, which lies within the proline-rich motif SPPP. Because phosphorylation of the A13 protein is only minimally affected by disruption of the viral F10 kinase or H1 phosphatase, a cellular kinase is likely to be involved. We generated an inducible recombinant in which A13 protein expression is dependent upon the inclusion of tetracycline in the culture medium. Repression of the A13L protein spares the biochemical progression of the viral life cycle but arrests virion morphogenesis. Virion assembly progresses through the formation of immature virions (IVs); however, these virions do not acquire nucleoids, and DNA crystalloids accumulate in the cytoplasm. Further development into intracellular mature virions is blocked, causing a 1,000-fold decrease in the infectious virus yield relative to that obtained in the presence of the inducer. We also determined that the temperature-sensitive phenotype of the viral mutant Cts40 is due to a nucleotide transition within the A13L gene that causes a Thr(48)→Ile substitution. This substitution disrupts the function of the A13 protein but does not cause thermolability of the protein; at the nonpermissive temperature, virion morphogenesis arrests at the stage of IV formation. The A13L protein, therefore, is part of a newly recognized group of membrane proteins that are dispensable for the early biogenesis of the virion membrane but are essential for virion maturation.